Women’s Non-Governmental Organizations in Contemporary Mongolia - S. S. Tsypilova (Oriental Studies, 2018)
The article deals with the history of the women's movement in modern Mongolia. In socialist Mongolia the women's movement  made a part of the state policies and was financed by the state  budget. It was the Committee of Mongolian Women that  implemented the main activities. Activities of women's organizations  in the socialist period were aimed at increasing the level of education of the female population of the country, improving the various  aspects of women's lives, stimulating their participation in the public  administration of the country. Special attention was paid to the  protection of maternity and infancy. The first independent women's  organizations appeared in Mongolia in 1992. The formation of the first women's organizations in 1992 was caused by a number of  interrelated reasons and factors. In view of the dramatic changes in the country, many educated middle-aged women found themselves in unfavorable working conditions. Women were underrepresented in economic and political realms, the key positions were traditionally  occupied by men. So, for some women non-governmental  organizations became the only opportunities for self-realization. It  should be noted that the women's movement in Mongolia — like  those in other Asian countries — developed in collaboration with  foreign organizations. The article aims to analyze the activities of the first women's NGOs of post-socialist Mongolia. The activities of women's NGOs in Mongolia strive for the solution of gender issues. Those also aim to help people adapt to the new social and economic  system and make use of its advantages. Among the main goals of  women's NGOs the following ones can be noted: assistance to  women in their cultural and social development, improvement of  living standards, promotion of women's participation in  decisionmaking issues, provision of social protection. The activities  and influence of women's non-governmental organizations have increased greatly in present-day Mongolia. They are getting actively involved in legislative undertakings, especially when it comes to  issues of unemployment, informatization and other problems on local and national levels. Their activities also include the fi ght against  violence towards women which is an obvious problem for the modern Mongolian society. Mongolian women's NGOs constitute a  decentralized, suffi ciently dense network of organizations. However,  the variety of interests and fields of activities allow women's NGOs to implement common projects with other organizations in different spheres.